NEUROTIC INFLUENCER – FEELING RULES AND THE AFFECTIVE PRACTICE OF ANXIETY IN SOCIAL MEDIA INFLUENCER WORK - Lehto, Mari Tellervo (AoIR Selected Papers of Internet Research, 2020)
Through in-depth qualitative interviews of four Finnish influencer mothers and online observation of their social media accounts, the presentation asks how influencers negotiate the feeling rules that govern (maternal) femininity on social media and attempt to cope with the emotional weight of precarious social media work. My data do not allow for the possibility of generalization but are rich, nuanced, and offer insight into ambivalent lived experiences and emotional pressures of ‘do what you love and love what you do’ ethic where emotional investment in one’s work encompasses all areas of life. The talk suggests that although anxiety can be considered a negative side effect of stressful social media work, sharing it on social media can also be understood as a tactic that plays a central role in the lifestyle influencer industry. I argue for using the affective practice (Wetherell, 2012, 2014) of anxiety as a theoretical concept to explore the influencers’ routinized emotional behaviour in their attempts to decrease the discrepancy between their emotions and cultural expectations. Drawing on Vik Loveday’s (2018) analysis of the “neurotic academic”, I suggest that the construction of an entrepreneurial influencer self is underpinned by anxiety. This argument is formulated through the figure of the “neurotic influencer” that is the embodiment of the ambivalent nature of gendered influencer work. Anxiety strives the influencers to exceed themselves all the while creating relatable social media subjects.